SANG KLONING YANG KUASA PRODUKSI DAN REPRODUKSI BARE LIFE DALAM FILM US - Abi Ihsanullah; Badri Badri; Winda Eka Pahla Ayuningtyas (Universitas Aki, 2021)
The aims of this study are to reveal how the forming processes of sovereignty through state of exception so it appears bare life, and how homo sacer attempt to face sovereign state in US movie. This analyses are focuses on political issues in American society under American government which is reflected in US movie. Political issues are taken up by analyzing the political movement which is taken by the goverment. After analyzing the political policies taken by the government, this research will reveal production and reproduction through state of exception in creating sovereign state. State of exception refers to ethnic and racist. This research uses of Jordan Peele's US movie and theory of sovereign & bare life according to Giorgio Agamben. This research applies descriptive qualitative method. The findings are the government gives different treatment to their citizens. The government gives special treatment to the society in general, while they exception and discrimination against the tethered. Exception and discrimination are the impact of the adaptation of law in order to fulfill the society needs.